2017
DOI: 10.1097/md.0000000000006380
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of using serum D-dimer for diagnosis of acute intestinal ischemia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
16
0
3
Order By: Relevance
“…In 2017, a meta-analysis performed by Sun et al included more studies (12 studies; 1300 patients), eight of which concerned AMI. The four other studies dealt with acute strangulated intestinal obstruction, acute intestinal necrosis and mixed types of acute intestinal ischemia, which could be gathered into the term "acute intestinal ischemia"; the calculated sensitivity and specificity were 94% and 50%, respectively [149]. D-dimer measurement could hence be useful for identifying patients with AMI.…”
Section: Acute Mesenteric Ischemiamentioning
confidence: 99%
“…In 2017, a meta-analysis performed by Sun et al included more studies (12 studies; 1300 patients), eight of which concerned AMI. The four other studies dealt with acute strangulated intestinal obstruction, acute intestinal necrosis and mixed types of acute intestinal ischemia, which could be gathered into the term "acute intestinal ischemia"; the calculated sensitivity and specificity were 94% and 50%, respectively [149]. D-dimer measurement could hence be useful for identifying patients with AMI.…”
Section: Acute Mesenteric Ischemiamentioning
confidence: 99%
“…The inclusion of both occlusive and non-occlusive forms of i3, as discussed in the larger paper of Matsumoto et al [33], could lead, however, to high heterogeneity in patients. However, a recent meta-analysis estimated the area under the curve (AUC) of the receiver operating curve (ROC) of D-dimer to 0.81, underlying its potential utility in clinical practice [35].…”
Section: Biological Markers Of Thrombosismentioning
confidence: 99%
“…In 2009, a prospective, non-interventional study showed the median D-dimer level in acute mesenteric ischemia was 6240 ng fibrinogen equivalent units (FEU)/mL, with a range from 960 to 5348 ng FEU/mL. In 2017, Da-Li Sun et al reported that the combined sensitivity was 94%, the specificity was 50%, the positive likelihood ratio was 1.9, the negative likelihood ratio was 0.12, the diagnostic odds ratio was 16 and the area under the curve (AUC) was 0.81 for a total of 1300 patients studied [4]. In our case, the elevated D-dimer of up to 3548.18 ng/mL may have been a hint for the physicians to attempt to identify the cause, such as pulmonary embolism, aorta dissection, and acute mesenteric infarction.…”
Section: Discussionmentioning
confidence: 99%